(untitled) (Journal of Organizational Psychology, 2017)
This paper uses economic measures of behavior to examine the validity of the line drawn between individuals inside and outside the labor force, particularly between the unemployed and those outside the labor force. If labor force states are indistinguishable, the unemployment rate is open to interpretation. Our findings suggest that labor force statuses are distinct for mature adults and less distinct for teenagers. However, among mature adults, the degree of distinctiveness varies by race and ethnicity. Since 1990, there has been increased instability between the labor force statuses of the unemployed and those outside the labor force in some groups.